Implementation of the Qur'an Surat Al-Isra' Version 23-25 in the Development of Muslim Family - Siti Mutiara Salsabila Karya Putri; Ajat Rukajat; Yayat Herdiana M (Edumaspul: Jurnal Pendidikan, 2021)
The Qur'an is an inexhaustible source of educational pearls. In the Qur'an there are very many texts or verses that guide and educate humans, because the purpose of the Qur'an was revealed to guide and direct humans to the right path. This research is motivated by the attention of researchers who are interested in the study "Implementation of Qs Al-Isra 'verse 23-25 ​​in Muslim Family Development". In this study, the main focus is the meaning of Birul Walidain, which means being devoted to both parents, doing good to both of them implies loving, loving, praying and being obedient and obedient to what is ordered. This research uses the type of library research or literature review. The data collection method used is the documentation method, while the analysis used is the content analysis method, which is a method that uses systematic techniques to analyze message content and process messages. The results of the research that researchers can conclude are in terms of interpretation in verses 23-25 ​​indicating that parents have a very high, honorable and great position in the sight of Allah SWT.